Black patients and women have reduced access to liver transplantation for alcohol‐associated liver disease. Issue 3 (30th March 2023) - Kaplan, Alyson; Wahid, Nabeel; Fortune, Brett E.; Verna, Elizabeth; Halazun, Karim; Samstein, Benjamin; Brown, Robert S.; Rosenblatt, Russell
Abstract : Although sex and racial disparities for liver transplantation (LT) are known, it is unclear if disparities exist for patients with alcohol‐associated liver disease (ALD). We aimed to compare sex and racial/ethnic differences in mortality, LT listing, and LT rates in patients with and without ALD. We analyzed patients who were listed for LT and/or died of end‐stage liver disease (ESLD) between 2014 and 2018 using the United Network for Organ Sharing Standard Transplant Analysis and Research and Centers for Disease Control and Prevention Wide‐ranging OnLine Data for Epidemiologic Research databases, respectively. Patients with ALD were compared with non‐ALD patients. Our primary outcome was the ratio of listings for LT to deaths from ESLD—listing‐to‐death ratio (LDR)—a previously derived metric to assess access to the waiting list. Differences between sex and race/ethnicity were analyzed with chi‐square tests and multivariable linear regression. There were 65, 588 deaths and 16, 133 listings for ALD compared with 75, 020 deaths and 40, 194 listings for non‐ALD. LDR was lower for ALD (0.25 vs. 0.54; p < 0.001). Black patients had the lowest LDR in both ALD and non‐ALD (0.13 and 0.39 for Black patients vs. 0.26 and 0.54 for White patients; p < 0.001). Women with ALD had a lower LDR (0.21 vs. 0.26; p < 0.001), whereas women without ALD had higher LDR than men (0.69 vs. 0.47; p < 0.001). There were significant negative interactions between women and ALD in LDR and the transplant‐to‐death ratio. Multivariable analysis and a sensitivity analysis, with more liberal definitions of ALD and non‐ALD, confirmed these findings. Patients with ALD have lower access to LT. Among those with ALD, female and Black patients have the lowest access. New initiatives are needed to eliminate these inequities.